Mr. Keating’s Role as English Teacher as Seen in The Main Character of Dead Poet Society the Movie - M. Afifulloh (Lire Journal)
Dead Poets Society is a classic movie that explores about English teaching-learning class in Welton Academic. Mr. Keating as the main character is described as unusual English teacher who gives a big influence toward his students’ life. This unusual teaching style absolutely opposites with academic policy. The academic administrator intensively warns Mr. Keating about his teaching style although his student very interested on him. This paper attempts to explore Mr. Keating’s roles as teacher as reflected in Dead Poets Society movie. The paper was qualitative study with American studies approach. American studies is multidisciplinary studies of America. In this multidisciplinary approach, the writer uses sociology, psychology and historical approaches to conduct the result of the research. Sociology and psychology are used to explain the roles of teacher in teaching and historical approach is used to explore all data dealt with American teacher fact in the past. The data was collected by various sources; text book, newspaper, internet and some available printed master.